2016
DOI: 10.1155/2016/4943793
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of 18β-Glycyrrhetinic Acid onHelicobacter pylori-Infected Gastric Mucosa in Mongolian Gerbils

Abstract: 18β-Glycyrrhetinic acid (GRA), a major component of Glycyrrhiza glabra, is widely used therapeutically in clinic. In this study, the effect of GRA on Helicobacter pylori- (H. pylori-) infected gastritis was investigated in Mongolian gerbils in vivo. The gerbils were randomly divided into groups: uninfected; H. pylori-infected; H. pylori + antibiotics (clarithromycin, amoxicillin, and esomeprazole); and H. pylori + GRA. The gastric intraluminal pH value, histopathological changes, and the expression levels of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“… 45 , 46 Several studies have suggested that autophagy serves as a cell survival mechanism in GA-treated cancers. 47 , 48 Consistent with these findings, the current study indicated that inhibition of JNK/c-jun pathway or GA-induced autophagy significantly increased apoptosis rates and cell death, suggesting GA- induced cytoprotective autophagy in sarcoma cells. However, IRE1 α knockdown failed to elicit an increase in GA-induced cell apoptosis ( Supplementary Figure S2 ) that may be attributed to the activation of both autophagy and apoptosis by IRE1 α .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“… 45 , 46 Several studies have suggested that autophagy serves as a cell survival mechanism in GA-treated cancers. 47 , 48 Consistent with these findings, the current study indicated that inhibition of JNK/c-jun pathway or GA-induced autophagy significantly increased apoptosis rates and cell death, suggesting GA- induced cytoprotective autophagy in sarcoma cells. However, IRE1 α knockdown failed to elicit an increase in GA-induced cell apoptosis ( Supplementary Figure S2 ) that may be attributed to the activation of both autophagy and apoptosis by IRE1 α .…”
Section: Discussionsupporting
confidence: 83%
“…The 18 β -glycyrrhetinic acid (GA), the major bioactive component in licorice root, exerts antioxidative, anti-inflammatory, and anticancer effects; 7 , 8 , 9 in patients with ovarian and breast cancers, the GA-containing Hongdoushan capsule (CHC) has been clinically used as an effective therapeutic strategy. 10 Furthermore, previous studies have demonstrated that GA suppresses tumor cell growth in breast, 8 lung, 11 and gastric 12 cancers.…”
mentioning
confidence: 99%
“…The 18 β-glycyrrhetinic acid (GRA) ( Fig. 1), a pentacyclic triterpenoid extracted from the root of Licorice, has been shown to display multiple physiological functions, such as anti-microbial (1,2), anti-inflammatory (3,4), anti-viral (5), anti-ulcer (6) and hepatoprotective effects (3). Recently, the antitumor effect of GRA has been extensively investigated in vitro and in vivo in breast (7,8), ovarian cancer (9), promyelocytic leukemia (10), hepatoma and stomach cancer cells (11).…”
Section: Introductionmentioning
confidence: 99%
“…According to Krausse et al (), the compounds responsible for this activity are glabridin and glabrene. Cao et al () also reported that 18β‐glycyrrhetinic acid significantly attenuated the gastritis infection caused by H. pylori . Asha et al () found that the flavonoid glabridin exhibits activity against H. pylori whereas glycyrrhizin did not present activity even at a concentration of 250 μg/ml.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%